Statin therapy reduces contrast-induced nephropathy: an analysis of contemporary percutaneous interventions - Khanal, Sanjaya; Attallah, Nizar; Smith, Dean E; Kline-Rogers, Eva; Share, David; O'Donnell, Michael J; Moscucci, Mauro (The American journal of medicine, 2005)
We sought to examine whether statin therapy before percutaneous coronary intervention results in reduction in contrast-induced nephropathy (CIN). Intravascular administration of contrast media can have nephrotoxic effects, particularly in patients with baseline renal insufficiency. Along with lowering serum cholesterol, statins have pleiotropic effects in the vasculature. The effect of statin use on CIN is unknown. We studied 29409 patients who had both baseline preprocedure and peak postprocedure serum creatinine measured at the time of their percutaneous coronary intervention (PCI). Baseline demographics and creatinine profile before and after the procedure were compared between patients who received preprocedure statins and those who did not. CIN was defined as an increase in serum creatinine of < or =0.5 mg/dL. Baseline serum creatinine was similar between the two groups. When compared with patients who did not receive preprocedure statins, patients on preprocedure statins had a lower incidence of CIN (4.37 vs 5.93, P <0.0001) and nephropathy requiring dialysis (0.32 vs 0.49, P = 0.03). After adjustments for comorbidities, preprocedure statin use was associated with a significant reduction in CIN (odds ration [OR] 0.87, 95% confidence interval [CI] 0.77-0.99, P = 0.03). Preprocedure statin use is associated with significant reduction in CIN after contemporary PCI. This reinforces the need to initiate statin therapy before percutaneous coronary interventions.